Regulation of Intestinal Epithelial Cells Properties and Functions by Amino Acids - Kong, Shanshan; Zhang, Weiqiang; Zhang, Yanhui H. (BioMed research international, 2018)
Intestinal epithelial cells (IECs) line the surface of intestinal epithelium, where they play important roles in the digestion of food, absorption of nutrients, and protection of the human body from microbial infections, and others. Dysfunction of IECs can cause diseases. The development, maintenance, and functions of IECs are strongly influenced by external nutrition, such as amino acids. Amino acids play important roles in regulating the properties and functions of IECs. In this article, we briefly reviewed the current understanding of the roles of amino acids in the regulation of IECs’ properties and functions in physiological state, including in IECs homeostasis (differentiation, proliferation, and renewal), in intestinal epithelial barrier structure and functions, and in immune responses. We also summarized some important findings on the effects of amino acids supplementation (e.g., glutamine and arginine) in restoring IECs’ and intestine functions in some diseased states. These findings will further our understanding of the important roles of amino acids in the homeostasis of IECs and could potentially help identify novel targets and reagents for the therapeutic interventions of diseases associated with dysfunctional IECs.